INTEGRATION OF GIS AND HEC-RAS IN FLOODS MODELING OF THE OUERGHA RIVER, NORTHERN MOROCCO - Abdelbasset, Midaoui; Abderrahim, Lahrach; Abdel Ali, Chaouni; Abdellah, Bourak; Lahcen, Benaabidate; Laila, Boukharas (European Scientific Journal, ESJ, 2015)
In recent years, hydrological hazards continue to worsen due to climate changes affecting the whole world. In Morocco, after a long period of severe drought that has ravaged the country since the eighties, the last years were exceptionally rainy. Records have been exceeded in terms of rainfall and flooding that affected many parts of the country. The Ouergha River, contributing with 50% of total water yield of the Sebou basin which is one of the most important watersheds in Northern Morocco, broke all records in 2009/2010 providing an exceptional amount of water of 7,4 109 m3. In this study, one-dimensional hydraulic modeling with HEC-RAS®, allowed to calculate the water flow profiles for some flood events that occurred downstream of Al Wahda dam. The exploitation of obtained results led to establish flood extension maps for each calculated profile, which made it possible to evaluate the management of the dam by the Sebou hydraulic Basin Agency. This type of results acquired from the hydraulic simulation and geographic information system, can significantly contribute in flood management interventions against overflows that persist despite the existence of a large dam (Al Wahda), because of extreme climatic and hydrologic events observed in recent years.